(untitled) (Indian Journal of Public Health Research & Development, 2020)
To understand diseases at a deeper level, we propose the concept of dispersed organisms as those having their constituent units spatially, and may be even temporally, separated in existence but still conforming to the definition of being an organic wholeness, having functionally dependent and non-spatio-temporally interconnected components. A living organism is characterized by elementary units (cells), each having the same DNA. This definition though specifically valid for multicellular complex organisms (eukaryotes), can very well be extended to include localized bacterial colonies as is evidenced by the phenomenon of quorum sensing, even though the DNA may only be partially identical. Starting with quorum sensing in bacteria as a preliminary indication, quantum entanglement among component units deriving from the same initial cause as a possible explanation, we draw upon a specific deeper vision of the causes of the Spanish flu pandemic of 1918-20 to establish the concept of dispersed organisms. We discuss the COVID-19 pandemic as a similar dispersed organism with its specific targets, severity, endemicity, span and consequences.